Strategi Pengembangan Kawasan Ekowisata Tepian Sungai Tallo di Makassar - Muhammad Ikhsan Andi (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
The tallo river area is a combination of land and water territories. Tallo river area also has multiple functions, such as irrigation water supplier and alternative tourism destination. Related to that, the tourism concept developed in tallo river area must be the one that can support the main functions of the river as an irrigation water supplier and support land conservation. Ecotourism is a tourism concept that supports conservation efforts. This kind of tourism highly appreciate historical and cultural environment, also local inhabitants participation. Ecotourism development in tallo river area is conducted as an effort to expand tourism that can support the river’s preservation. The aims of the research are to (1) find out the potency ecotourism area in Tallo riverside, (2) formulate the developed strategy to make use of Tallo River the development of ecotourism in makassar city. The research was a descriptive study. The methods of obtaining the data were observation, interviews and documentation. The data were analyzed qualitative. The results of the research reveal that the strategies to develop natural potency are to build ecological village and environmental friendly garden, to improve accessibility in the tallo riverside such as to build spermonde tourism piers, and to provide vocation that is in accordance with ecotourism needs in Tallo River. Further research needs doing especially eco-hydraulics in river areas.